The Citizen's Ephemerides of the Physiocrats - Wasserman, Max J.; Tate, Juanita D. (Quarterly Journal of Economics, 1951)
Journal Article The Citizen's Éphémérides of the Physiocrats Get access Max J. Wasserman, Max J. Wasserman Howard University, Washington, D.C. Search for other works by this author on: Oxford Academic Google Scholar Juanita D. Tate Juanita D. Tate Howard University, Washington, D.C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 65, Issue 3, August 1951, Pages 439–443, https://doi.org/10.2307/1882225 Published: 01 August 1951